Strategi Agricultural-Demand-Led-Industrialization dalam Perspektif Peningkatan Kinerja Ekonomi dan Pendapatan Petani - Sri Hery Susilowati (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2008)
EnglishThe new paradigm of agricultural development placed Agricultural-Demand-Led-Industrialization (ADLI) strategy as an industrialization strategy emphasizing agriculture development program and setting the agriculture sector as a prime mover of industry and other sectors. The strategy is considered appropriate to be applied in developing countries which agriculture sector is their main resource. This paper aims to analyze the role of ADLI strategy in developing countries, including Indonesia, on macroeconomic performance and on farmers and land less households’ income improvement. The main result of this study is that ADLI strategy has an important role on macroeconomic performance, especially on labor absorption, GDP improvement as well as on other sector’s income acceleration. However, the strategy is quite a distance from an ideal implementation in terms of household income distribution. The benefit gained from agriculture and agroindustry sector development was mostly pour to non agriculture households in urban areas while farmer’s households and especially those of landless gained the least.IndonesianParadigma baru pembangunan pertanian menempatkan strategi Agricultural-Demand-Led- Industrialization (ADLI) sebagai strategi industrialisasi yang menitikberatkan program pembangunan di sektor pertanian dan menjadikan sektor pertanian sebagai penggerak pembangunan sektor industri dan sektor-sektor lain. Strategi pembangunan ini dipandang sesuai diterapkan di negara-negara berkembang yang memiliki sumberdaya utama di sektor pertanian. Makalah ini bertujuan untuk menelaah peran strategi ADLI yang telah diterapkan di negara-negara berkembang termasuk Indonesia dalam meningkatkan kinerja ekonomi makro dan meningkatkan pendapatan rumah tangga petani dan buruh tani. Kesimpulan pokok dari kajian ini adalah bahwa strategi ADLI berperan baik khususnya dalam penyerapan tenaga kerja, peningkatan PDB dan perannya dalam mengakselerasi pertumbuhan sektor-sektor lain. Namun dalam hal distribusi pendapatan rumah tangga, strategi ADLI masih jauh dari penerapan yang ideal. Manfaat pengembangan sektor pertanian primer dan agroindustri lebih banyak mengalir ke rumah tangga nonpertanian di kota, sedangkan buruh tani dan petani menerima pendapatan terkecil.